Cacophony in conceptualizing and operationalizing ethnicity: the case of Roma in Hungary. - Messing, Vera; Pap, András L. (Ethnic & Racial Studies, 2024)
Using secondary research from the political, education, and employment fields, this paper aims to demonstrate the consequences of confused and overlapping conceptualizations of the Roma in Hungary as an ethnic group, a racialized minority, a national minority, and a socially disadvantaged group. The resulting cacophony of operationalizing schemes blurs clarity and constrains efficient measures for inclusion policies. In social sciences and law, the purpose of classification is to help us understand the internal logic of concepts. Thus, classification has significant consequences, as it can imperil policy goals. Through examining the case of the Hungarian Roma, the article demonstrates how the confused conceptualization of ethnicity, race, and nationality and ill-applied methods of operationalization have vastly detrimental consequences. In addition, it is argued that many concerns regarding ethnic data processing that policy actors voice are legally unfounded, and pre-existing data protection regimes allow the processing of ethno-racial data.